Estado del arte de la aplicación Cobit en Pymes. - Sánchez Chávez, Alberto Paúl (2016)
The growth of technological advances in today’s world is unstoppable, so, if SMEs want to be at the forefront and have an advantage over their competitors, they must acquire and implement IT, since with it, they will be able to optimize time and resources, but for reaching that, it is not enough to possess IT assets, but manage them properly; that is why it was considered that SMEs may require a framework and control IT Governance, such as COBIT. Based on these criteria, with a sample of SMEs in Quito - Pichincha – Ecuador, it was investigated how much and how SMEs apply COBIT as a framework to govern and manage their IT. Additionally, because of the purpose of the study is state of art, other research sources were considered to integrate a body of knowledge about using the COBIT framework in this type of business. Finally, the results of this research, it is the aim of the project to support and encourage other research initiatives that help understand and improve IT management in SMEs.